Surgical morbidity and mortality in patients with calculus biliary tract diseases - Khan, Zubair Afzal (International Surgery Journal, 2019)
Background: In the era of laparoscopic cholecystectomy the discussion on morbidity and mortality of open cholecystectomy still holds importance and should not be considered obsolete. The values of good anaesthesia, good muscular relaxation, adequate operative exposure and adequate stretch on the CBD and careful anatomical dissection are very well known. The objective of the study was to study the surgical morbidity and mortality in patients with calculus biliary tract diseases. Methods: The study included 839 patients with surgical jaundice and various surgical modalities applied as per the need and indication. 168 patients out of 839 were referred to Department of General Surgery for surgical management. Results: The commonest surgical procedure carried out was cholecystectomy with CBD exploration in 102 (60.71%) patients. Only CBD stone was found in 79 (47.02%) patients. Total 43 (25.60%) incidence of post-operative complications were reported in the patients. Surgical wound infection (20, 11.90%) was the commonest post-operative complications, followed by chest infection (13, 7.74), and biliary leakage (4, 2.38%). Four (2.38%) deaths were reported among 168 cases. Conclusions: Conventional surgeries like CBD exploration, choledochoduodenostomy (CDD), choledochoju-jenostomy (CDJ), transduodenal sphincteroplasty (TDS) can be associated with morbidity and mortality in spite of optimisation and excellent postoperative care.